2011
DOI: 10.1037/a0025620
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of interpersonal violence against community-living adults with disabilities: A literature review.

Abstract: IPV occurs at elevated and disproportionate rates among women and men with disabilities, especially when assessed over the course of their lives. Future research that relies on standard definitions of disability and violence, uses accessible measurement, and examines IPV in diverse populations of people with disabilities will strengthen future reviews and better inform research and policy priorities on disability and violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(100 citation statements)
references
References 39 publications
(294 reference statements)
4
95
0
1
Order By: Relevance
“…The findings from this study are consistent with earlier studies that have shown that people with disabilities are at higher risk for various forms of violence victimization (Barrett et al, 2009;Casteel et al, 2008;K. Hughes et al, 2012;R. L. Hughes et al, 2011;Martin et al, 2006;Mitra, Lu, et al, 2012;Mitra et al, 2011;Brownlie, et al, 2007;Oktay & Tompkins, 2004;Sullivan et al, 1987;Nannini, 2006), and that violence victimization is associated with negative health and health risk behaviors (Black et al, 2011;Coker et al, 2002;Coker et al, 2000;Mitra, Mouradian, et al, 2012;Resnick et al, 1997).…”
Section: Discussionsupporting
confidence: 93%
“…The findings from this study are consistent with earlier studies that have shown that people with disabilities are at higher risk for various forms of violence victimization (Barrett et al, 2009;Casteel et al, 2008;K. Hughes et al, 2012;R. L. Hughes et al, 2011;Martin et al, 2006;Mitra, Lu, et al, 2012;Mitra et al, 2011;Brownlie, et al, 2007;Oktay & Tompkins, 2004;Sullivan et al, 1987;Nannini, 2006), and that violence victimization is associated with negative health and health risk behaviors (Black et al, 2011;Coker et al, 2002;Coker et al, 2000;Mitra, Mouradian, et al, 2012;Resnick et al, 1997).…”
Section: Discussionsupporting
confidence: 93%
“…With regard to the first goal, men in our sample had similar abuse disclosure rates as those reported in the small existent body of literature on IPV of MWD (Hughes et al, 2011;Powers et al, 2008). This exploratory study found lifetime rates of physical abuse of MWD to be 45.2%, which is slightly lower than the 65% rate of lifetime physical abuse found in Powers et al's (2008) sample of MWD; however, rates of lifetime sexual abuse were similar across these two studies: 22.6% in this study and 24% in Powers et al's (2008) sample.…”
Section: Summary and Discussionsupporting
confidence: 82%
“…Promising research on trauma-informed interventions such as Seeking Safety has revealed its effectiveness with women with physical disabilities; however, the study's authors acknowledge the need for more research with a larger, more diverse sample of women with disabilities (Anderson & Najavits, 2014). Diversity is notably lacking in previous studies of IPV among women with disabilities (Hughes et al, 2011), which tend to represent mainly white, college-educated women. Prior research by this team (Ballan et al, 2014) indicates that women with disabilities who seek IPV services are substantially more diverse than those sampled in abuse and disability research, and underscores the need to examine distinct groups of women with disabilities.…”
Section: Resultsmentioning
confidence: 57%
“…Literature on violence and women with disabilities has included a range of disabilities in the study sample, yet generally fails to examine abuse among specific disability groups (Hughes et al, 2011). It is essential for intervention methods to account for the interplay of disability, abuse, and related psychosocial dimensions, and acknowledge how these factors impact the health, well-being, and options of women with disabilities (Copel, 2006).…”
Section: Lessons From Past Researchmentioning
confidence: 99%